Penyelenggaraan rekam medik balai pengobatan rumah sakit gigi dan mulut program studi kedokteran gigi fakultas kedokteran universitas sam ratulangi manado - Kalara, Edwin N (e-GiGi, 2014)
Abstract: Completemedical recordcanprovidelegal protection forphysicians, dentists andmedical personnelin the event ofcertain cases. Dental medical records have critical data that needs to be recorded, summarized in the dental medical record sheet so that it serves as a check list for patients. Such as the identity of the patient, the patient's general condition, odontogram, Dental care data and the name of the treating dentist, so the medical record is crucial in analyzing a forensic case and as a primary proof of accurate, also in terms of improving quality of care. The purpose of this study was to determine the organization of medical records on BP-RSGM Dentistry Study Program Faculty of Medicine, University of  Sam Ratulangi Manado . The population  in this study were medical records in BP - RSGM University of Sam Ratulangi from a period of 3 weeks in a row on the 27th August to 14th September 2012 . The results showed that the procedure for the implementation of medical records at the BP-RSGM University of Sam Ratulangi begin receiving patient registration, medical records filling up on pengarsipannya is already pretty good. It was referring to the organization of the medical record that the guidelines issued by the Ministry of Health in 2006. Keywords: medical records Abstrak: Rekam medis yang lengkap dan jelas dapat memberikan perlindungan hukum bagi dokter, dokter gigi dan tenaga medis ketika terjadi kasus-kasus tertentu. Rekam medis gigi memiliki data-data penting yang perlu dicatat  dan dirangkum dalam lembar rekam medis gigi sehingga berfungsi sebagai check list untuk pasien. Seperti identitas pasien, keadaan umum pasien, odontogram, data perawatan Kedokteran Gigi dan nama dokter gigi yang merawat, sehingga rekam  medis merupakan hal yang sangat menentukan dalam menganalisa suatu kasus forensik dan sebagai alat bukti utama yang akurat, juga dalam hal peningkatan mutu pelayanan. Tujuan penelitian ini adalah untuk mengetahui penyelenggaraan rekam medis pada BP RSGM Program Studi Kedokteran Gigi Fakultas Kedokteran Universitas Sam Ratulangi Manado. Populasi dalam penelitian ini adalah rekam medis di BP-RSGM Universitas Sam Ratulangi Manado dari kurun waktu 3 minggu berturut turut pada tanggal 27 Agustus sampai 14 September 2012. Hasil penelitian menunjukkan bahwa tatacara penyelenggaraan rekam medis di BP RSGM Universitas Sam Ratulangi mulai pendaftaran penerimaan pasien, pengisian rekam medis sampai pada pengarsipannya adalah sudah cukup baik. Hal tersebut sudah mengacu pada pedoman penyelengaraan rekam medis yang dikeluarkan oleh Departemen Kesehatan RI tahun 2006.Kata kunci : rekam medis